2002
DOI: 10.1017/s1355617702870096
|View full text |Cite
|
Sign up to set email alerts
|

Decline in verbal memory during preclinical Alzheimer's disease: Examination of the effect of APOE genotype

Abstract: A subtle decline in episodic memory often occurs prior to the emergence of the full dementia syndrome in nondemented older adults who develop Alzheimer's disease (AD). The APOE-epsilon4 genotype may engender a more virulent form of AD that hastens this decline. To examine this possibility, we compared the rate of decline in episodic memory during the preclinical phase of AD in individuals with or without at least one APOE epsilon4 allele. Nondemented normal control (NC; n = 84) participants, nondemented older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
113
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(121 citation statements)
references
References 71 publications
8
113
0
Order By: Relevance
“…Similar results have been described in AD patients with left temporal and/or hippocampal damage, where a subtle decline in episodic memory occurs prior to the emergence of full dementia. The presence of the APOE‐ ε 4 allele increases deposition of beta‐amyloid plaques, and has been shown to independently contribute to the prediction of conversion dementia when measured by tests of episodic memory such as the CVLT‐II (Lange et al., 2002). …”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been described in AD patients with left temporal and/or hippocampal damage, where a subtle decline in episodic memory occurs prior to the emergence of full dementia. The presence of the APOE‐ ε 4 allele increases deposition of beta‐amyloid plaques, and has been shown to independently contribute to the prediction of conversion dementia when measured by tests of episodic memory such as the CVLT‐II (Lange et al., 2002). …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have now shown that subtle cognitive changes can precede the diagnosis of AD by a few years or more (Bäckman et al, 2001;Bondi et al, 1994Bondi et al, , 1995Bondi et al, , 1999Chen et al, 2001;Lange et al, 2002;Linn et al, 1995;Masur et al, 1994;Rubin et al, 1998;Small et al, 1998Small et al, , 2000Smith et al, 1998). As Sliwinski and colleagues (1996) have shown, the inclusion of such individuals with preclinical AD in a normative sample leads to an underestimate of the mean, an overestimate of the variance, and an overestimate of the effect of age on a given cognitive measure, all of which reduces the sensitivity of the measure for detecting mild impairment.…”
Section: Discussionmentioning
confidence: 99%
“…If this is the case, previously observed differences in the clinical and neuropsychological presentation of YoungOld AD patients with or without the ε4 allele (Lange et al, 2002;Smith et al, 1998) may be absent or changed in Very-Old AD patients. Several studies that have compared cognitive deficits in predominantly Young-Old AD patients with or without the ε4 allele suggest that those with the ε4 allele may have generally more severe memory impairment (Smith et al, 1998) or less ability to use strategic processes or semantic abilities in support of memory (Lange et al, 2002) than those without the ε4 allele, even when duration of illness and severity of global dementia is comparable. A decrease in the influence of the APOE ε4 allele on the manifestation of AD in the Very-Old may attenuate these differences and modify the profile of cognitive deficits that characterizes the disease.…”
Section: Introductionmentioning
confidence: 92%
“…Some of the free recall data for the CONVs presented in Table 2 were previously analyzed by Lange et al (2002) as part of an unrelated investigation of the effect of apolipoprotein E (ApoE) genotype on verbal memory. Unless otherwise noted, an alpha level of .05 was used throughout.…”
Section: Tmt-a and Tmt-bmentioning
confidence: 99%